Chemical Assignment of Structural Isomers of Sulfur-Containing Metabolites in Garlic by Liquid Chromatography−Fourier Transform Ion Cyclotron Resonance−Mass Spectrometry. Issue 2 (13th January 2016) - Nakabayashi, Ryo; Sawada, Yuji; Aoyagi, Morihiro; Yamada, Yutaka; Hirai, Masami Yokota; Sakurai, Tetsuya; Kamoi, Takahiro; Rowan, Daryl D; Saito, Kazuki
Abstract: Background: The chemical assignment of metabolites is crucial to understanding the relation between food composition and biological activity. Objective: This study was designed to detect and chemically assign sulfur-containing metabolites by using LC−Fourier transform ion cyclotron resonance−mass spectrometry (FTICR-MS) in Allium plants. Methods: Ultrahigh resolution (>250, 000 full width at half-maximum) and mass accuracy (<1 mDa) by FTICR-MS allowed us to distinguish ions containing sulfur isotopes ( 32 S and 34 S). Results: Putative 69 S-containing monoisotopic ions (S-ions) were extracted from the metabolome data of onion ( Allium cepa ), green onion ( Allium fistulosum ), and garlic ( Allium sativum ) on the basis of theoretical mass differences between 32 S-ions and their 34 S-substituted counterparts and on the natural abundance of 34 S. Eight S-ions were chemically assigned by using the reference data according to the guidelines of the Metabolomics Standards Initiative. Three ions detected in garlic were assigned as derived from the isomers γ-glutamyl- S -1-propenylcysteine and γ-glutamyl- S -2-propenylcysteine and as S -2-propenylmercaptoglutathione on the basis of differences in key product ions identified in reference tandem MS spectra. Conclusion: The ability to discriminate between such geometric isomers will be extremely useful for the chemical assignment of unknown metabolites in MS-based metabolomics.